ESTIMATION OF GENETIC DIVERGENCE AMONG THE NIGER GERMPLASM - R. Bisen; A. K. Panday; S. Jain; R. Sahu; M. Malviya (Journal of Animal and Plant Sciences, 2016)
A study was conducted to assess the genetic divergence among the 100 niger germplasm on the basis of morphological and quantitative traits at Project Coordinating Unit (Sesame & Niger), JNKVV, Jabalpur. Genetic distance between clusters was calculated using the generalized Mahalanobis D2 statistics and grouped the germplasm into seventeen clusters based on divergence analysis. Cluster II was the largest among all clusters comprising 36 germplasm followed by Cluster I having fifteen germplasm, Cluster III having fourteen germplasm, cluster XII having twelve germplasm and cluster IV having eleven germplasm. Clusters V, VI, VII, VIII, IX, X, XI, XIII, XIV, XV, XVI and XVII had single germplasm each. Among the traits studied, seed yield contributed maximum towards genetic divergence (72.53%) followed by days to maturity (12.10%), number of capitula per plant (7.29%) and 1000 seed weight (4.71%). Moderate to low contribution was exhibited by plant height followed by oil content and lowest contribution was given by number of branches per plant. The highest intra cluster distance was recorded in cluster XII followed by cluster III. The inter cluster distance was highest between the cluster XIV and cluster IV followed by cluster VIII and cluster IV. The lowest inter cluster distance was observed between cluster VII and cluster VI. Cluster XVII comprising of germplasm N- 139 exhibited highest mean values  for seed yield per plant, number of branches/plant, oil content, plant height, number of capitula per plant and days to maturity. Cluster XVI comprising of germplasm N- 18 exhibited lowest mean values for plant height, number of capitula per plant, 1000 seed weight and oil content. Crossing between germplasms lying in cluster XIV and cluster IV followed by cluster VIII and cluster IV, cluster XVI and cluster IV i.e. N- 11, N- 3, N- 580, N- 103, N- 51, N- 13, N- 38, N- 15, N- 33, N- 52, N- 114, N- 140, N- 102, N- 18 may be desirable for getting superior hybrids/recombinants.
Keywords: Niger; divergence; clusters; crossing; hybrids